Graphic Interlude: Reinventing the Sea - Geetha Ganapathy-Doré; Ludmila Volná; Walter Raleigh; Aristide Maillol; Joni Sternbach; David Cox (Angles)
This graphic interlude features pictures illustrating this issue’s topic: the sea as symbol, metaphor and unit of analysis.